Environmental Management Accounting Information and Environmental Performance, the Mediating Effect of Environmental Decision Quality - Asa’d, Mutasim; Ahmad, Wan Norhayati Wan; Ayoup, Hazeline (International Journal of Energy Economics and Policy, 2024)
In recent times, there has been a heightened focus from both governments and societies towards evaluating Organisations’ Environmental Performance (OEP). Environmental Management Accounting (EMA) is pivotal in elevating OEP as it offers a holistic perspective to elucidate the environmental impacts and associated costs of diverse business activities. This research delves into the dynamic interplay between EMA information and the OEP. The study entails the administration of a questionnaire to Jordanian organisations listed on the Amman Stock Exchange. The research adopts the Resource-Based View Theory. The study establishes statistically significant positive connections between these variables by employing partial least square structural equation modelling (SEM) for data analysis. Central to this investigation is identifying Environmental Decision Quality (EDQ) as a mediating capability. This capability is the mechanism for translating the relationship between EMA information and OEP. This finding underscores the pivotal role of in-formed decision-making in converting such information into tangible improvements in environmental performance. The research makes a notable contribution by expanding the understanding of EMA, highlighting its informational value beyond merely the practice considerations. Moreover, findings provide invaluable guidance for policymakers and regulatory bodies striving to promote sustainable business practices, especially pertinent in the context of developing nations.